Ritonavir increases loperamide plasma concentrations without evidence for P-glycoprotein involvement - Tayrouz Haffar, Yorki Antoine; Ganßmann, Beate; Ding, Reinhard; Klingmann, Andrea; Aderjan, Rolf; Burhenne, Jürgen; Haefeli, Walter E.; Mikus, Gerd (Clinical pharmacology & therapeutics, 2001)
Background The antidiarrheal drug loperamide is frequently used to treat ritonavir-associated diarrhea in patients with human immunodeficiency virus. The absence of marked central opioid effects has been attributed to its low bioavailability and its poor penetration of the blood-brain barrier, both of which might be altered by ritonavir, a potent P-glycoprotein and cytochrome P4503A inhibitor. Methods A 16-mg dose of loperamide was administered to 12 healthy male and female volunteers together with either 600 mg of ritonavir or placebo. Detailed pharmacokinetics of loperamide and its metabolites were determined over 72 hours. Central opioid effects were measured by evaluation of pupil diameter, cold pressor test, and transcutaneous PCO2 and PO2. Results Ritonavir caused a major pharmacokinetic interaction, increasing the area under the concentration-time curve of loperamide from 104 ± 60 h · pmol/ml after placebo to 276 ± 68 h · pmol/ml and delayed formation of the major metabolite desmethylloperamide (time to reach maximum concentration after drug administration [tmax], 7.1 ± 2.6 hours versus 19.6 ± 9.1 hours). The urinary metabolic ratio of loperamide increased 3 times whereas the total molar amount of loperamide and metabolites excreted in urine remained unchanged. No central pharmacodynamic effects were observed after coadministration of loperamide with either ritonavir or placebo. Conclusion This study demonstrates a major metabolic interaction probably by cytochrome P4503A4 with no evidence of P-glycoprotein involvement. This might explain the lack of central effects after ritonavir. Clinical Pharmacology & Therapeutics (2001) 70, 405-414; doi: 10.1016/S0009-9236(01)35864-2